مهارسة استراتيجيات التنمية لهنية وعلاقتها بأداء لهارات الأدارية لديري مدارس التعليم الأساسي بسلطنة عمان - Balushi Ali Hassan Abdullah (Universiti Sains Islam Malaysia, 2024)
This study aims at analyzing the level of professional development strategies practice for the principals of basic education schools in the Sultanate of Oman. It also analyses the relationship between this practice and the performance of managerial skills for the population in question. Then the study provides suggestions on enhancement of professional development strategies and management skills’ performance. The study used the descriptive correlational method. The study sample consisted of (285) principals in basic education schools in the Sultanate of Oman selected by the simple random sampling procedure. The researcher used a questionnaire which consisted of five axes: professional development strategies, cognitive conceptual management skills, technical management skills, personal management skills The results of the study further revealed a statistically significant correlation at the alpha level (α=0.05) between the exercise of professional development strategies and the managerial skills for the principals of basic education schools in the Sultanate of Oman. Based on the results the study recommended more engagements in the practice of professional development strategies so as to improve the professional development and management skills mechanisms for the principals of basic education schools in the Sultanate of Oman.